Case report: Pericardial effusion complicated by tamponade - Michele Montandon; Rae Wake; Stephen Raimon (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2012)
Pericardial effusion is fluid in the space between the heart and the pericardial sac. There are many causes of pericardial effusion, with infection (viral and TB) as the most common. If fluid rapidly accumulates in the pericardial space, like in chest trauma, this fluid can compress the heart (cardiac tamponade) and cause circulatory failure. With slow accumulation of fluid, the pericardial sac will stretch to accommodate the fluid. However, if fluid continues to accumulate, tamponade will eventually occur. This is an emergency situation requiring aspiration of pericardial fluid (pericardiocentesis).